The perfect corporate board : a handbook for mastering the unique challenges of small-cap companies - Epstein, Adam (McGraw-Hill, 2013)
Offering best practices designed specifically for smaller companies; this book identifies the key challenges board members of smaller companies face on a routine basis; and it provides the solutions to resolve them. --